2019
DOI: 10.1111/crj.12982
|View full text |Cite
|
Sign up to set email alerts
|

Pleura revisited: From histology and pathophysiology to pathology and molecular biology

Abstract: Pleural cavity has an interesting physiology that when impaired gives rise to pleural effusions a rather frequent problem in respiratory medicine practice. Their aetiology varies widely producing distinct pathological lesions with different prognosis and treatment. The basic morphological features of pleural diseases, neoplastic and nonneoplastic, will be analysed in this review with an emphasis to their pathophysiology, differential diagnosis and clinicopathological correlations. K E Y W O R D Sgenetics, infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The results were consistently homogeneous and revealed that murine mesothelioma are rich in infiltrating myeloid cells (mainly macrophages). This high content of tumor-associated macrophages well reflects the inflammatory micro-environment that characterizes also human MPM [ 16 , 17 , 18 , 19 ]. One tumor cell line (AB12) was also rich in T lymphocytes, which is an interesting finding in consideration of a potential response to checkpoint-based immunotherapy treatments, currently under clinical investigation in patients [ 7 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were consistently homogeneous and revealed that murine mesothelioma are rich in infiltrating myeloid cells (mainly macrophages). This high content of tumor-associated macrophages well reflects the inflammatory micro-environment that characterizes also human MPM [ 16 , 17 , 18 , 19 ]. One tumor cell line (AB12) was also rich in T lymphocytes, which is an interesting finding in consideration of a potential response to checkpoint-based immunotherapy treatments, currently under clinical investigation in patients [ 7 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the use of human cells is appreciable for a translation relevance, the tumor graft was below 70%, while in our experience the injection of murine tumor cells in syngeneic mice was 100% (in 50 mice). Furthermore, the use of immunodeficient mice, as mentioned above, cannot provide information on the role of the immune system in disease progression and in the anti-tumor response to conventional or immunotherapeutic treatments [ 16 , 19 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This p16 overexpression has diagnostic utility in these pathologies. In other forms of cancer, like mesotheliomas or melanomas, there is a genetic inactivation of p16 , and it is this detection that has diagnostic significance, 10,14,15 while in several other tumors, wild-type or mutant p16 overexpression is observed and associated with more aggressive neoplasms, but through unknown mechanisms. 16 p16 overexpression in these cases may be an attempt to restore p16 functions, but its negative impact on cellular proliferation can be avoided or prevented by alternative molecular events.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, until that time, the "atypical mesothelial hyperplasia" probably corresponded to difficult to diagnose cases, and not necessarily to a truly pre-invasive disease. However, in the most recent years, new ancillary techniques became available [84], such as BAP1 loss in immunohistochemistry and CDKN2A homologous deletion identified by FISH or by its surrogate MTAP cytoplasmic immunohistochemical expression that allowed to diagnose mesothelial malignancy more confidently. Given the more reliable diagnosis achieved with the aid of these techniques, interest regarding the possibility of pre-invasive lesions to exist has been renewed.…”
Section: Non-specific Pleuritismentioning
confidence: 99%